UNDERSTANDING THE ROLE OF THE HIDDEN CURRICULUM IN THE SOCIAL CONSTRUCTION OF GENDER IN SINGLE SEX COLLEGES: THE CASE STUDY OF FEMALE PUBLIC COLLEGE STUDENTS IN PAKISTAN - Shakir, Rakhshinda (Nazarbayev University Graduate School of Education, 2024)
In the pursuit of exploring the formal curriculum and its role in constructing gender roles, it has often been neglected to understand the informal or hidden curriculum in the social construction of gender. This research explored the hidden curriculum's influence within Pakistani single-sex public colleges on the development and expression of gender roles and identities. The study was based on a qualitative case study employing a phenomenological research framework to explore how the hidden curriculum in single-sex colleges in Pakistan impacts girls’ educational experiences, agency, and navigation of obstacles. Using Seidman’s structure for the in-depth phenomenological interviewing method and employing semi-structured interviews as a data collection instrument, this research explored students current and aspirational possible selves, their perception of possible feared selves, social and cultural influence, and empowerment and agency to navigate obstacles. Possible selves, gender, and hidden curriculum are the three theoretical concepts used in the study, and the findings of this research offer a window into female students’ perspectives and encounters concerning the hidden curriculum’s influence on gender within the educational realm and provide insightful implications for educational policymakers and practitioners, highlighting the importance of considering hidden curriculum awareness within specific educational contexts.
Keywords: Type of access: Open Access